Interaction between ACTN3 (r577x), ACE (i/d), and BDKRB2 (-9/+9) polymorphisms and endurance phenotypes in brazilian long-distance swimmers - Neto, S. L. d. A.; Herrera, J. J. B.; Rosa, T. S.; de Almeida, S. S.; Silva, G. C. B.; Ferreira, C. E. S.; dos Santos, M. A. P.; Silvino, V. O.; de Melo, G. F. (The Journal of Strength and Conditioning Research, 2022)
This study investigated the interactions between the polymorphisms ACTN3 (R577X), ACE (I/D), and BDKRB2 (-9/+9) and their association with endurance phenotypes in Brazilian long-distance swimmers. Twenty-six volunteers (aged 18-30 years) were divided into 2 groups as follows: 19 subelite athletes formed the pool swimming experts (PSE: 400-1500 m) group and 7 elite athletes the open water swimming experts (OWSE: 5-25 km) group. ACTN3 (R577X), ACE (I/D), and BDKRB2 (-9/+9) polymorphisms were genotyped through polymerase chain reaction. A nonathletes control (CON) group derived from studies with the Brazilian population was created. Hardy-Weinberg equilibrium (X2) was observed in all groups. The total genotype score (TGS) associated with endurance phenotypes was used in this study. A significance level was established at p = 0.05. PSE and CON groups had very similar genotyping distribution. The OWSE group had a greater frequency for the genotypes XX (57.1%), ID (57.1%), and the alleles X (71.4%) and I (57.2%) than CON and PSE groups (XX = 21.1 and 21.1%; ID = 47.1 and 52.6% [p > 0.05]; X = 44.0 and 42.1%; I = 45.3 and 42.1%, respectively). Considering BDKRB2, OWSE and PSE groups had a greater frequency of +9/+9 than the CON group (42.9% and 31.6 vs. 27.5%, respectively). Although the expected genotypic distribution was not verified among athletes, the TGS revealed small supremacy of 3-5 typical alleles in the OWSE group (54.8 ± 26.7%) compared with the PSE group (41.2 ± 17.8%) (p = 0.072; confidence interval = 95%; effect size = 0.95). The OWSE group seem to have benefited from the best genotype profile verified for ACTN3 and ACE. However, the results of this work should be approached with caution because of the small number of athletes and polymorphisms assessed.